Protocol for a Cluster-Randomized Controlled Trial on the Effectiveness of Fluoride Varnish in Preventing Dental Caries Among Rural School Children in Namkum, Ranchi - Swati Sharma; Ajoy K. Shahi; Subhash Chandra; Nishita Garg; Shantala R. Naik; Sonal Saigal; Subhankar Dubey; Tanveer Rehman (Journal of Pharmacy and Bioallied Sciences)
Background: Dental caries is a prevalent oral health issue among children, particularly in underserved rural areas. This cluster-randomized controlled trial aims to assess the effectiveness of fluoride varnish in preventing caries in first permanent molars among schoolchildren in Namkum, Ranchi. Methods: A total of 600 children (6–7 years old) from 16 rural schools will be randomized into intervention (fluoride varnish) and control groups. Caries status will be assessed using the Caries Assessment Spectrum and Treatment (CAST) criteria over 24 months. Expected Outcomes: The study aims to demonstrate a reduction in caries incidence and improved oral hygiene behaviors, supporting fluoride varnish as a preventive public health measure.